2005
DOI: 10.1007/s00018-005-5378-7
|View full text |Cite
|
Sign up to set email alerts
|

Increased mitochondrial palmitoylcarnitine/carnitine countertransport by flavone causes oxidative stress and apoptosis in colon cancer cells

Abstract: Cancer cell metabolism is characterized by limited oxidative phosphorylation in order to minimize oxidative stress. We have previously shown that the flavonoid flavone in HT-29 colon cancer cells increases the uptake of pyruvate or lactate into mitochondria, which is followed by an increase in O(2) (-.). production that finally leads to apoptosis. Similarly, a supply of palmitoylcarnitine in combination with carnitine induces apoptosis in HT-29 cells by increasing the mitochondrial respiration rate. Here we sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 24 publications
2
13
0
Order By: Relevance
“…Diminished mitochondrial oxidation of acetyl-CoA from glucose and fatty acid breakdown is a hallmark of cancer cell metabolism. Because low mitochondrial respiration also reduces the reactive oxygen species (ROS) burden, tumour cells appear to be particularly well protected from oxidative stress (Wenzel et al 2005). Redirecting cancer cell metabolism towards a normal phenotype could therefore result in specific apoptosis induction by an increased ROS production (Wenzel et al 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Diminished mitochondrial oxidation of acetyl-CoA from glucose and fatty acid breakdown is a hallmark of cancer cell metabolism. Because low mitochondrial respiration also reduces the reactive oxygen species (ROS) burden, tumour cells appear to be particularly well protected from oxidative stress (Wenzel et al 2005). Redirecting cancer cell metabolism towards a normal phenotype could therefore result in specific apoptosis induction by an increased ROS production (Wenzel et al 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the inhibition of alanine aminotransferase, that slows down aerobic glycolysis and promotes an increase in cellular respiration by the oxidation of glutamine, has been shown to diminish cellular as well as tumor growth (8). Since cancer cell metabolism is characterized by a limited activity of oxidative phosphorylation to minimize oxidative stress during proliferation (10,15), a likely mechanism that explains the preferential death of cancer cells when forced to oxidize mitochondrial substrates is by the overproduction of superoxide radical as a result of the stimulation of mitochondrial metabolism (8,98).…”
Section: The Tumor Suppressor Function Of Mitochondrial Activitymentioning
confidence: 99%
“…In this regard, the oxidation of mitochondrial substrates is known to halt malignant growth. The oxidation of fatty acids by the mitochondrial b-oxidation pathway is known to engage cancer cells into death (7,98). Moreover, the inhibition of alanine aminotransferase, that slows down aerobic glycolysis and promotes an increase in cellular respiration by the oxidation of glutamine, has been shown to diminish cellular as well as tumor growth (8).…”
Section: The Tumor Suppressor Function Of Mitochondrial Activitymentioning
confidence: 99%
“…RSV appears to prevent oxidation of low-density lipoprotein (LDL) by chelating copper and scavenging ROS. Furthermore, a RSV-rich diet has been demonstrated to produce a measurable increase in plasma antioxidant level and decreased lipid peroxidation (103). It has also been reported that RSV reduces intracellular ROS and prevents LDL oxidation in endothelial cells (104).…”
Section: Resveratrol As a Potent Antioxidantmentioning
confidence: 99%